Spatio‐temporal patterns of foot‐and‐mouth disease transmission in cattle between 2007 and 2015 and quantitative assessment of the economic impact of the disease in Niger. Issue 4 (5th March 2018) - Souley Kouato, B.; Thys, E.; Renault, V.; Abatih, E.; Marichatou, H.; Issa, S.; Saegerman, C.
Summary: Foot‐and‐mouth disease (FMD) is endemic in Niger, with outbreaks occurring every year. Recently, there was an increasing interest from veterinary authorities to implement preventive and control measures against FMD. However, for an efficient control, improving the current knowledge on the disease dynamics and factors related to FMD occurrence is a prerequisite. The objective of this study was therefore to obtain insights into the incidence and the spatio‐temporal patterns of transmission of FMD outbreaks in Niger based on the retrospective analysis of 9‐year outbreak data. A regression tree analysis model was used to identify statistically significant predictors associated with FMD incidence, including the period (year and month), the location (region), the animal‐contact density and the animal‐contact frequency. This study provided also a first report on economic losses associated with FMD. From 2007 to 2015, 791 clinical FMD outbreaks were reported from the eight regions of Niger, with the number of outbreaks per region ranging from 5 to 309. The statistical analysis revealed that three regions (Dosso, Tillabery and Zinder), the months (September, corresponding to the end of rainy season, to December and January, i.e., during the dry and cold season), the years (2007 and 2015) and the density of contact were the main predictors of FMD occurrence. The quantitative assessment of the economic impacts showed that the average total cost of FMD at outbreak level was 499 euros, while the average price for FMD vaccination of one outbreak was estimated to be more than 314 euros. Despite some limitations of the clinical data used, this study will guide further research into the epidemiology of FMD in Niger and will promote a better understanding of the disease as well as an efficient control and prevention of FMD.